Os Guarani: o tempo das andanças acabou? Conflitos entre ficar e partir - Cabral, Ana Cristina Bochnia (2016)
For the Guarani in the western region of Paraná, the land is historically related to the sacred, having in itself an own meaning of its people. It is an area of free movement, where the Indians exercise their cultural practices and beliefs, producing their culture and making reference to their symbolic world. The land is one of the elements that constitute the identity of the group, being, therefore a factor that characterizes its cultural diversity. With the onset of the recent colonization and its principles of ownership and exploitation of the territory, these people were denaturalized in the name of Christian faith and civilization. The problem of territory and especially the identity of these people worsened from the time understood as the border definition. Today, the land conflicts generated between the Guarani and the settlers in the border region of West of Paraná oppose possession of the territory traditionally occupied to the newly colonized one. This work, product of an ethnographic survey in the Tekohá Y'Hovy village, located in the city of Guaíra, Paraná, Brazil, seeks to demonstrate the relationship that the Guarani have with the land, a territory without demarcation. One of the striking features of this indigenous group is their mobility. This study aims to examining how they have worked the issue of displacement in times where settling becomes the best option, or even the only possible one.